Current strategies in multiphasic scaffold design for osteochondral tissue engineering: A review. Issue 7 (11th November 2014) - Yousefi, Azizeh‐Mitra; Hoque, Md Enamul; Prasad, Rangabhatala G. S. V.; Uth, Nicholas
Abstract: The repair of osteochondral defects requires a tissue engineering approach that aims at mimicking the physiological properties and structure of two different tissues (cartilage and bone) using specifically designed scaffold–cell constructs. Biphasic and triphasic approaches utilize two or three different architectures, materials, or composites to produce a multilayered construct. This article gives an overview of some of the current strategies in multiphasic/gradient‐based scaffold architectures and compositions for tissue engineering of osteochondral defects. In addition, the application of finite element analysis (FEA) in scaffold design and simulation of in vitro and in vivo cell growth outcomes has been briefly covered. FEA‐based approaches can potentially be coupled with computer‐assisted fabrication systems for controlled deposition and additive manufacturing of the simulated patterns. Finally, a summary of the existing challenges associated with the repair of osteochondral defects as well as some recommendations for future directions have been brought up in the concluding section of this article. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103: 2460–2481, 2015.